Perlindungan Hukum Penyelenggara Peer to Peer Lending dalam Penagihan Wanprestasi Peminjam - Marliana, Gina; Al Baisar, Moch Teguh; Saputera, Khoirul Amri (UI Scholars Hub, 2026)
The rapid growth of the peer-to-peer (P2P) lending industry in Indonesia has increased financial access for the public and micro-businesses, but this has been accompanied by an increase in default risks that threaten the stability of the industry. This study analyzes the legal framework governing protection for P2P lending operators and ethical and legally compliant collection strategies when borrowers default. Various regulations, including the PDP Law, ITE Law, P2SK Law, POJK 10/2022, POJK 40/2024, and SE OJK 19/2023, stipulate that operators must implement strict governance, identity verification, personal data protection, and collection ethics. Although the risk of default is in principle borne by the lender, operators still have an administrative responsibility to ensure transparency, accuracy of credit assessment, and complaint mechanisms. The findings of the study show that problems arise from weak risk analysis, misuse of personal data as false collateral, default communities, and illegal collection practices. This study offers mitigation strategies, including regulatory harmonization, national guidelines for handling defaults, provision of insurance schemes, strengthening of internal governance, dispute resolution through mediation or arbitration, and the application of RegTech in supervision. This study concludes that the sustainability of the P2P lending industry requires a balance between innovation, consumer protection, and legal certainty.